BEBERAPA PENDEKATAN PERENCANAAN DALAM MENINGKAT RUMAH SEBAGAI SALAH SATU SOLUSI KETERBATASAN LAHAN - Rita Laksmitasari Rahayu (LPPM, 2010)
This article is a simple text which aims to find a strategy or the other term is to anticipate the additional space requirement. Conditions that completely narrow and small in our house, can be optimized size, that is in many ways, one of which is to increase home. However, there are some things to consider, in order to obtain results that truly fit with our desire, which is from government regulation, IMB, architecture, structure, and utilities. Establish, develop, and improve the house should consider the local government regulations in accordance with the location of the house, such as the Coefficient of Association Building (KDB), Coefficient Floor Building (KLB), Line Sepadan Building (GSB), this is to preserve the